1999
DOI: 10.1902/jop.1999.70.8.878
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Postsurgical Antibiotics and a Bioabsorbable Membrane on Regenerative Healing in Class II Furcation Defects

Abstract: The administration of postsurgical antibiotics did not produce statistically superior osseous healing of Class II furcation defects. This result may be attributable to membrane design which facilitates connective tissue ingrowth, thereby preventing bacterial downgrowth and contamination of the newly regenerated tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…The mean combined estimate that compared the resorbable with allograft and all other surgical procedures showed statistical improvements in outcomes of all four parameters (open flap debridement, 37 allograft against resorbable membranes with allograft ± antibiotic 40,44 ). The mean combined estimate showed a reduction in VPD of 0.81 ± 0.51 mm (95% CI, −0.20 to 1.81).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The mean combined estimate that compared the resorbable with allograft and all other surgical procedures showed statistical improvements in outcomes of all four parameters (open flap debridement, 37 allograft against resorbable membranes with allograft ± antibiotic 40,44 ). The mean combined estimate showed a reduction in VPD of 0.81 ± 0.51 mm (95% CI, −0.20 to 1.81).…”
Section: Resultsmentioning
confidence: 98%
“…Title or abstract reviews were completed for these publications, yielding a total of 40 studies from the online search and 14 from the hand search (total of 54 papers). Of the 54 papers, a full‐text review concluded that only 34 articles met the specified inclusion criteria for the meta‐analyses 31‐64 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A systemic antibiotic is usually prescribed after a GTR operation to reduce bacterial contamination and to prevent wound infection 15,21,22 . However, the results are not predictable 23,24 . Alternatively, the local application of antibiotics, including antibiotic solution irrigation, antibiotic gel, antibiotic fiber, or antibiotic‐loaded GTR membrane, 25–28 may be used during GTR therapy.…”
mentioning
confidence: 99%